Online purchasing behavior model : the exploration of protection motivation theory - Dita Aulia; M Ma’ruf; Eri Besra (Institute of Computer Science (IOCS), 2022)
This study aims to analyze the motivational theory of protection in Women’s fashion in the marketplace in Indonesia during Covid-19. The population in this study are women of the millennial generation who shop for women’s fashion at marketplaces in West Sumatra. The sampling method used is non-probability sampling using the purposive sampling technique. The total sample in the study was 130. Hypothesis testing using statistical analysis with two-tailed. The results of the study are that Threat Appraisal has a negative effect on the adaptive behavior of customers who shop online for women’s fashion in post-covid-19. Coping Appraisal has a positive effect on the adaptive behavior of customers who shop online for women’s fashion in the post-covid- 19. The relationship between threat appraisal and adaptive behaviour is negatively moderated by consumer resilience and satisfaction with the retailer’s assistive intent on customers who shop online for women’s fashion in the post-covid-19.